The Effect Of LEGO Games On Early Childhood Spatial Ability In Understanding Mathematical Concepts - Al Ayyubi, Ibnu Imam; Nurhikmah; Fitriani, Namiyah; Putra, Ari Limay Trisno; Hidayatullah, M. Baihaki (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This study aims to analyze the effect of LEGO games on early childhood spatial abilities and understanding of mathematical concepts. Through a quantitative approach, this study involved children aged 5-6 years at Kober Darul Amanah Kindergarten, West Bandung Regency with a population of all students in the school and a sample of 25 students selected randomly. This study uses a quantitative approach with a survey method and explanatory research design. This study is included in a causal-correlational study, which is a method to see the relationship or influence between variable X and variable Y without direct manipulation. The sampling technique used is probability sampling with the simple random sampling method. The results of the analysis showed that the data were not normally distributed, with a significance value of 0.017 for spatial ability and 0.016 for mathematical understanding. In addition, the correlation analysis produced a significance value of 0.378, which indicates that there is no significant relationship between LEGO games and increased spatial ability and understanding of children's mathematical concepts. These findings indicate that although LEGO play can be an educational tool, its use in this context is not effective enough to improve both aspects of cognitive development.